On the Ecological Niche of the West - Federico Leon (European Journal of Geography)
The Western Civilization, comprising Western Europe, the US, Canada, Australia, and New Zealand, challenges the definition of civilization as a group of populations sharing a common geographic locus. However, its locus may be biogeographic rather than geographic. This study examined whether Western European and transoceanic Western nations share a common ecological niche. Results across 145 countries indicate that high steady rainfall and low ultraviolet radiation characterize and differentiate an encompassing West from Europe to Oceania. Moreover, these meteorological variables help explain the West’s expansion from its inception to the Carolingian Empire and the present. Owing to their weaker steady rainfall, Italy, Spain, and Portugal form a peripheral West, suggesting the need to study their cultural differentiation from the core West. However, their northern provinces may be part of the core ecological West. Provincial-level research is needed to better delineate the West’s frontiers.